A CAUSAL MODEL OF PRODUCT DESIGN, TECHNICAL PERFORMANCE AND BRAND AWARENESS AS PREDICTORS OF CONSUMER PURCHASE INTENTIONS FOR SMART HOUSEHOLD ELECTRICAL APPLIANCES. - Zhou, Dewei; Sukpasjaroen, Khunanan (Scientific Culture, 2026)
To explore the key driving factors influencing consumers' purchase of smart home appliances, this paper constructs a causal model of consumer purchase intention, with product design, technical performance, and brand awareness as the core antecedent variables. By reviewing relevant literature and defining the dimensions of the variables, this paper collects samples through a questionnaire survey, selecting over five hundred consumers from mainstream online shopping platforms in China, such as JD.com, Tmall, Tiktok, and Pinduoduo. The reliability, validity, and mediating effect of the questionnaire are verified using Cronbach's alpha coefficient. The results confirm that consumers' focus on smart home appliances primarily lies in technical performance, operational convenience, brand, appearance, and other aspects. This study also provides a basis for home appliance enterprises in product research and development, technological improvement, and brand management, offering theoretical references for the healthy development of the home appliance industry.